2000
DOI: 10.1103/physrevd.62.084037
|View full text |Cite
|
Sign up to set email alerts
|

Power, energy, and spectrum of a naked singularity explosion

Abstract: It is well known that a naked singularity occurs in the gravitational collapse of an inhomogeneous dust ball from an initial density profile which is physically reasonable. In this paper we show that explosive radiation is emitted during the formation process of the naked singularity while we fix the background spacetime. The energy flux is proportional to (tCH − t) −3/2 for a minimally coupled massless scalar field, while it is proportional to (tCH − t) −1 for a conformally coupled massless scalar field, wher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Before this study, there are a lot of past studies about the observational feasibility of the super-spinning objects and/or naked singularity in a variety of astrophysical contexts such as; direct radio observations of a super-spinning Kerr object [4,29], accretion disc around a super-spinning Kerr object [64], gravitational lensing phenomena by a superspinning Kerr object [65,66,67,68], light rays from a forming naked singularity [69,70], particle creation (emission) from a forming naked singularity [59,60,61,62,71,72], gravitational radiation from a forming naked singularity [73,74,75,76], physical processes in naked singularity formation [63,77,78], connection to gamma-ray bursts (GRBs) [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…Before this study, there are a lot of past studies about the observational feasibility of the super-spinning objects and/or naked singularity in a variety of astrophysical contexts such as; direct radio observations of a super-spinning Kerr object [4,29], accretion disc around a super-spinning Kerr object [64], gravitational lensing phenomena by a superspinning Kerr object [65,66,67,68], light rays from a forming naked singularity [69,70], particle creation (emission) from a forming naked singularity [59,60,61,62,71,72], gravitational radiation from a forming naked singularity [73,74,75,76], physical processes in naked singularity formation [63,77,78], connection to gamma-ray bursts (GRBs) [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…Even for such an "approximate" naked singularity, it has been shown that explosive radiation is emitted due to quantum effects [36][37][38][39][40][41][42][43]. Furthermore, in a practical sense, if the curvature scale reaches the Planck scale, it should be regarded as a singularity because it is considered beyond the scope of classical general relativity.…”
Section: Discussionmentioning
confidence: 99%
“…, (2.37) 38) and 39) where C k is a constant determined by k as 40) and the parameter D is defined as…”
Section: Basic Equations a Einstein Equationmentioning
confidence: 99%
“…at past null infinity as an initial quantum state. Then, the function κ(u) determines radiation power regularized at future null infinity, through [20,26,32]…”
Section: Particle Creation In Spherically Symmetric Spacetimesmentioning
confidence: 99%